Daemons of the shadow realm. 8 - Arakawa, Hiromu, 1973- (Daemons of the shadow realm, 2025)
"Ancient Daemons awaken to fight a new battle in an age-old war!!Yuru finally joins the fray against Ivan, who proves to be a menace even when injured! Using his sharp tongue and even sharper reflexes, Ivan manages to get away-but not before taking a few more lives in the process. As the long night draws to a close, Yuru engages in heart-to-heart talks with both the fake and real Asas. Can they reconcile Higashi Village's sins from the past with their own hopes for the future?" --